Negative Difference Operator and Its Associated Sequence Space. (21st May 2021) - Roopaei, Hadi; Kara, Merve İlkhan
Abstract: Let Δ − n be the backward difference operator of order − n . In this paper, we study some properties of the matrix domain associated with this operator and after computing α -, β -, γ -duals, we characterize some matrix classes on this space. Moreover, we investigate the problem of finding the norm of well-known operators such as Cesàro and Hilbert from ℓ p ( Δ − n ) into ℓ p .